Real Wage Growth, Technical Change and Competition in the Labor Market - Leslie, Derek (The Review of Economics and Statistics, 1985)
The paper measures the rate of growth of average labor cost and the real wage for the twenty U.S. two digit manufacturing industries 1948-76. It is argued that these rates of growth give interesting information which other studies on the real wage ignore. The results suggest that the gains from technical advance are shared equally across all labor markets, consistent with the competitive paradigm. A simple and appealing rationale for the observation that high growth industries show the slowest relative rate of growth of prices is also given. T HE General Theory (Keynes, 1936) unleashed many controversies. One of the earliest and still topical controversy is the cyclical behavior of the real wage. Essentially the real wage-employment debate has focussed on whether or not the demand schedule slopes downwards and there have been many studies on this topic, producing a variety of conflicting findings.' A common feature of the real wage-employment studies is to abstract away from the growth in the real wage that is bound to occur in a growing economy. These studies are primarily concerned with deviations from trend or innovations in the real wage and the theme of this paper is that to ignore the growth in the real wage is to throw away valuable and interesting information. This information on real wage growth tells us a great deal about competition in the labor market. This study should be seen as being complementary, rather than conflicting, with the real wage-employment studies. The existence of a downward sloping demand curve for labor is, after all, not sufficient (and probably not necessary) for the functioning of competitive labor markets. Over the span of years 1948-76, I find that individual U.S. manufacturing industries record widely varying rates of productivity growth. However, these same industries tend to show a common rate of growth of the real wage. This feature of productivity growth was emphasized by the late Salter (1960) in his pathbreaking analysis of technical change. He writes, There is no tendency for above-average increases in labour productivity to be accompanied by above-average increases in earnings.